Reliability and Validity of the Boston Bedside Quantitative Sensory Testing Battery for Neuropathic Pain. Issue 10 (10th May 2020) - Koulouris, Alexandra E; Edwards, Robert R; Dorado, Kathleen; Schreiber, Kristin L; Lazaridou, Asimina; Rajan, Sharika; White, Jeffrey; Garcia, Jenniffer; Gibbons, Christopher; Freeman, Roy
Abstract: Objective: Recent studies suggest that sensory phenotyping may provide critical information for the diagnosis and management of patients with chronic neuropathic pain (NP). However, many formal quantitative sensory testing (QST) paradigms require expensive equipment, a dedicated location, and substantial time commitments on the part of patient and examiner, highlighting the need for a convenient and portable "bedside" QST battery. We developed and tested a bedside QST battery in a sample of patients with chronic NP. Methods: Participants (N = 51) attended two in-person visits over approximately two weeks, during which they underwent QST using both laboratory-based equipment and simple, easily accessible bedside tools. Participants also completed questionnaires about their daily pain and NP symptoms. Results: Test–retest reliability estimates were highly statistically significant and did not differ between bedside (mean r = 0.60) and laboratory-based (mean r = 0.72) QST. Bedside QST variables and corresponding laboratory-based QST variables were highly correlated, suggesting adequate criterion validity for the bedside tests. Conclusions: Results from the present study may have important implications for the sensory phenotyping and subsequent management of patients with chronic NP. Implementation of a protocol that uses inexpensive, portable, and convenient tools may allow for the application of QST in variety of clinical settings and advance NP research.